Proses Pembentukan Peraturan Daerah tentang Kawasan Tanpa Rokok di Kota Medan Tahun 2013 - Juanita Juanita (Jurnal Kebijakan Kesehatan Indonesia, 2014)
Background: The number of smokers in Indonesia is still high and in the absence of serious attention by government, then this problem would be a time bomb in the future. Results of previous studies have shown a variety of diseases associated with cigarette consumption. Medan city as the capital of North Sumatra province has been concerned with this problem and have proposed smoke- free zone regulation since 2010. However, the enactment of smoke-free zone regulation requires a long process and a strong commitment from the local government. Methods: The study design was a case study with a qualitative approach. Informants of this studyis the city of Medan legislators in charge of health, industry, labor, trade and agriculture. Data is collected using in-depth interview techniques to explore the views of relevant legislative regulation on smoke-free zone. Results: Stages of the process of establishing regulations smoke-free zone are: 1) the initiation stage than has been started since 2010 and was initiated by the Health Ministry, assisted by the city of Medan Indonesia Heritage Foundation, which is one of the NGOs involved in the protection of children and women. 2) discussion stage, which has been proposed (ranperda) until 2011 and has not been a priority for Parliament, because there is no political will to protect the public from the dangers of cigarette smoke. A discussion process regulation is the most crucial step to achieve a common understanding among the members of the legislature. 3) determination phase. After going through the long process through meetings (paripurna) in the decision making process and consent on smoke-free zone then the regulation is validated by approved by allfactions. 4) Promulgation phase, which is the issuance of Regulation No.3 of 2014 on smoke-free zone, which consists of 16 chapters 47 subchapters; and 5) Dissemination, socialisation of smoke free zone Regulation. Conclusion: The process of forming regulation of smoke- free zone through several stages, which initiated in 2010 by the Ministry of Health that began to organize activities related to problems of cigarettes. In the early stage, smoke-free zone regulation was not a priority to be discussedin meetings in Parliament, due to arising pros and cons. Commitment from the local government and community support are the factors that made this regulation be processed so that in December 2013 the Parliament plenary meeting pass the regulation and in January 2014 Regulation No.3 about smoke-free zone is issued. Recommendation: There are many challenges ahead after the issuance of regulation smoke-free zone. The regulation should be implemented effectively, with the involvement of relevant stakeholders, also society (citizens-based smoke- free zone enforcement). In addition, cross-sectoral cooperation in the application of smoke-free zone regulation needs to be improved. Ministry of Health as a driving force of smoke-free zone policies should support the necessary monitoring and evaluation. LatarBelakang: Jumlah perokok di Indonesia masih tinggi dan tanpa adanya perhatian serius pemerintah maka permasalahan ini akan menjadi bom waktu di masa depan. Hasil penelitian terdahulu sudah membuktikan berbagai penyakit terkait konsumsi rokok. Kota Medan sebagai ibukota Provinsi Sumatera Utara sudah sejak tahun 2010 menaruh perhatian terhadap masalah ini dan sudah mengusulkan Ranperda Kawasan Tanpa Rokok. Namun, hingga keluarnya perda KTR ini membutuhkan proses yang cukup lama dan komitmen yang kuat dari peme- rintah daerah. Metode:Desain penelitian ini adalah studi kasus dengan pen- dekatan kualitatif. Informan penelitian ini adalah anggota DPRD Kota Medan yang membidangi kesehatan, perindustrian, ketena- gakerjaan, perdagangan dan pertanian. Pengumpulan data de- ngan menggunakan teknik wawancara mendalam untuk meng- gali pandangan anggota legislatif terkait Perda KTR Kota Medan. Hasil: Tahapan proses pembentukan perda KTR Kota Medan adalah: 1) Tahap inisiasi yang sudah dimulai sejak tahun 2010 dan diprakarsai oleh Dinas Kesehatan Kota Medan dengan didampingi oleh Yayasan Pusaka Indonesia, yang merupakan salah satu NGO yang bergerak dalam perlindungan anak dan wanita. 2) Tahap pembahasan, ranperda yang sudah diusulkan hingga tahun 2011 belum merupakan prioritas bagi parlemen, karena belum ada political will untuk melindungi masyarakat dari bahaya asap rokok. Proses pembahasan suatu ranperda merupakan tahap yang paling krusial untuk mencapai pema- haman yang sama di antara anggota legislatif. 3) Tahap pene- tapan, setelah melalui proses yang panjang maka melalui rapat paripurna dalam rangka pengambilan keputusan dan persetu- juan bersama tasranperda KTR Kota Medan maka ranperda ini disahkan dengan disetujui oleh seluruh fraksi yang ada. 4) Tahap pengundangan, dikeluarkannya Perda No 3 tahun 2014 tentang KTR di Kota Medan, yang terdiri dari 16 bab 47 pasal; dan 5) Tahap Penyebarluasan melalui Seminar Pembela- jaran Implementasi Regulasi KTR di Indonesia. Kesimpulan: Proses terbentuknya Perda KTR di Kota Medan melalui beberapa tahap yang dimulai sejak tahun 2010 dimana Dinas Kesehatan mulai mengadakan kegiatan-kegiatan terkait permasalahan rokok. Pada tahap awal, ranperda KTR belum menjadi prioritas untuk dibahas dalam rapat-rapat di DPRD, karena timbul pro dan kontra terhadap ranperda ini. Adanya komitmen dari pemerintah daerah dan dukungan dari masyarakat agar perdaini segera diproses sehingga pada bulan Desember 2013 dalam rapat paripurna DPRD perdaini disahkan dan pada bulan Januari tahun 2014 telah dikeluarkan Perda KTR No 3 tentang KTR di Kota Medan. Rekomendasi :Tantangan kedepan setelah dikeluarkannya Perda KTR Kota Medan adalah agar perda ini dapat diimple- mentasikan secara efektif, dengan melibatkan para stakeholder terkait juga masyarakat (penegakan KTR berbasis warga). Selain itu juga kerjasama lintas sektoral dalam penerapan Perda KTR perlu ditingkatkan. Dinas Kesehatan sebagai motor penggerak implementasi Perda KTR perlu melakukan monitor- ing dan evaluasi.